Seed production of Bituminaria bituminosa: size, production, retention and germination capacity of the legumes - Correal E.; Hoyos A.; Ríos S.; Méndez P.; Real D.; Snowball R.; Costa J. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Bituminaria bituminosa, a Mediterranean and Macaronesian pasture legume, presents a large genetic diversity, with 3 botanical varieties (bituminosa, albomarginata and crassiuscula). A breeding and screening process started to recombine desirable traits currently dispersed in pre-selected populations and natural hybrids of the three before-mentioned varieties. Additionally, the domestication of B. bituminosa as a new pasture legume will require producing seed at the lowest cost. To achieve this objective, it is necessary to search for plant diversity in relation to seed production, fruit retention and germination capacity of the harvested seeds. Preliminary data showed that B. bituminosa produces large quantities of seeds, but in general, they shed easily and present low germination capacity (about 20% without scarification). However, selected accessions such as Calnegre, Tahonilla and Cañadas Teide, present good seed retention (50-70% after 50 days of fruit ripening) and germination values improved to 80% when scarified.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)